Mathematical Design of Coil Parameter for Wireless Power Transfer using NI Multisims Software - Yusoff, Siti Hajar; Nanda, Nadia Nazieha; Midi, Nur Shahida; Badawi, Ahmed Samir Abed (IEEE, 2021)
This paper presents a new design of circular coil for both primary and secondary sides in wireless power transfer (WPT). This paper starts with the numerical solution of 500W power for ideal case WPT to calculate the values of coil parameters for both primary and secondary sides. The optimum value of coupling coefficient (k) was verified by k < kc where kc is the critical coupling coefficient. After that, this paper designs the schematic circuit of this project by using all component values from the previous step. The circuit is then simulated by using NI Multisims software to obtain the measured values of the coil parameters. Next, this paper discusses the power efficiency between calculated and measured values. Finally, the summary of the suitable dimensions for inner and outer diameters and the number of turns needed for both primary and secondary coils are calculated by using the values of inductance.